EKSISTENSI BADAN PERENCANAAN PEMBANGUNAN DAERAH DALAM MENGELOLA ASPIRASI MASYARAKAT - Franky Djafar (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
This study aims to determine the ability of the Regional Development Planning Agency in absorbing community aspirations in development planning, and the factors that support and hinder it. This research uses qualitative by taking the research setting or location in Gorontalo Regency. Data collection techniques were carried out using interviews, observation and documentation. Data analysis in this study used analytical techniques with interactive patterns. The results of the study show that the Development Planning Agency still has difficulties in accommodating and accommodating community aspirations through the development planning system so that the results have not been able to fulfill all existing aspirations. in the form of communication has not been able to support the management of community aspirations to run well. Factors supporting the Regional Development Planning Agency in absorbing community aspirations are coordination between stakeholders, availability of information technology, stakeholder participation, and the authority possessed by the institution. While the inhibiting factors are the capabilities and skills of the apparatus, the minimum quality of apparatus resources, political intervention from the authorities, elite domination in setting programs, and the low quality of proposals from the community.